ECO-FRIENDLY TECHNOLOGY-KEY FOR SUSTAINABLE DEVELOPMENT - Tundele, Sarika (International Journal of Research -GRANTHAALAYAH, 2015)
Environmentally friendly technology is a rapidly growing field that focuses on new scientific and technical methods that benefit the earth. Also referred to as “green technology,” this area is dedicated to preserving our natural resources. This involves both the development of new technologies and the improvement of existing ones. While these inventions, improvements, and scientific developments can have a worldwide impact on our global ecosystem, they also affect people on an individual level. Many green technologies directly affect the everyday lives of those who use them. By improving the way people perform basic tasks such as cooking, cleaning, or heating and cooling their home, green technologies are able to reduce the environmental impact that families have on the earth every day. Environmentally friendly technology utilizes many methods for reducing the impact that various activities have upon the earth. To be considered environmentally friendly, a product or action should be sustainable, produce as little waste and pollution as possible, and utilize the recycling and reuse of materials whenever possible.